Migration aspirations in Ukraine: Human rights violations as migration drivers - Yuliya Borshchevska (University of Warsaw, Centre of Migration Research (CMR), 2014)
Ukraine is ranked highly among emigration countries and in particular among countries supplying labor migrants to the EU and Russia. The slumping economy and deteriorating political situation with an increasing number of authoritarian traits logically evoke the question of how non-economic motivation factors impact migration aspirations in Ukraine. The worsening human rights situation in the country is, in a way, seen as a separate matter and is not always associated with migration. This article is aimed to explore whether human rights violations exert an impact on the migration aspirations of people in Ukraine, in the context of a continually stagnant Ukrainian economy. Economy and human rights are not taken here as different ends of the spectrum; in particular, human rights are not reduced to "physical integrity rights". This topic is studied based on a case study which included 4 research locations in Ukraine, which differ with respect to their migration profile.
Keywords: 330; migration; migration aspirations; human rights; economic factors; Ukraine